2005
DOI: 10.2105/ajph.2004.044305
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Maternal and Perinatal Risk Factors Reported on Fetal Death Certificates

Abstract: We sought to estimate the accuracy, relative to maternal medical records, of perinatal risk factors recorded on fetal death certificates. We conducted a validation study of fetal death certificates among women who experienced fetal deaths between 1996 and 2001. The number of previous births, established diabetes, chronic hypertension, maternal fever, performance of autopsy, anencephaly, and Down syndrome had very high accuracy, while placental cord conditions and other chromosomal abnormalities were reported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 14 publications
3
33
0
1
Order By: Relevance
“…Several studies have shown that, while early fetal deaths tend to be under-reported (Goldhaber, 1989), lower gestational age reporting requirements improve ascertainment for cases !20 weeks gestation (MacDorman et al, 2007). Studies also have demonstrated that certain information (e.g., the presence of a birth defect, or placental or cord conditions) in these records is often incomplete and inaccurate (Greb et al, 1987;Lydon-Rochelle et al, 2005). Furthermore, population-based data on the causes and risk factors for stillbirth are scarce (Pauli et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that, while early fetal deaths tend to be under-reported (Goldhaber, 1989), lower gestational age reporting requirements improve ascertainment for cases !20 weeks gestation (MacDorman et al, 2007). Studies also have demonstrated that certain information (e.g., the presence of a birth defect, or placental or cord conditions) in these records is often incomplete and inaccurate (Greb et al, 1987;Lydon-Rochelle et al, 2005). Furthermore, population-based data on the causes and risk factors for stillbirth are scarce (Pauli et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, birth certificates were observed to be invalid or unreliable sources of information for tobacco use, alcohol use, and prenatal care (Northam and Knapp, 2006). Lydon-Rochelle (2005) compared data from fetal death certificates to medical records, and confirmed the accuracy of variables including the number of previous births, the number of prior pregnancies, chronic hypertension, and established diabetes history to be highly accurate. Among eight reports of fetal deaths, a 100% true-positive rate and a 50% true-positive rate for pre-gestational and gestational diabetes, respectively, were observed (LydonRochelle, 2005).…”
Section: Discussionmentioning
confidence: 84%
“…Fifth, the accuracy of vital statistics data has well-known limitations, especially in regard to patient conditions before pregnancy; the coding of these conditions is less sensitive than that for procedures. [23][24][25][26] Finally, misclassification or residual confounding may have affected our results. There are also differences in completion of birth certificates according to birth setting, 2,25,27 and the accuracy of the reporting of many demographic and clinical variables is unknown.…”
Section: Discussionmentioning
confidence: 96%